Comparison of international arbitration rules - Kerr, J. J (JurisNet, LLC, 2008)
Compares the arbitral rules of: International Chamber of Commerce (ICC), American Arbitration Association/International Chamber of Commerce (AAA/ICDR), London Court of International Arbitration (LCIA), Stockholm Chamber of Commerce (SCC), and International Center for Settlement of Investment Disputes (ICSID).